Strategic resource dependence - Reyer Gerlagh; Matti Liski (Fondazione Eni Enrico Mattei (FEEM), 2008)
We consider a situation where an exhaustible-resource seller faces demand from a buyer who has a perfect substitute but there is a time-to-build delay for the substitute. We that find in this simple framework the basic implications of the Hotelling model (1931) are reversed: over time the stock declines but supplies increase up to the point where the buyer decides to switch. Under such a threat of demand change, the supply does not reflect the true current resource scarcity but leads to increased future scarcity, felt during the transition to the substitute supplies. The analysis suggests a perspective on costs of oil dependence.
Keywords: D4; D9; O33; Q40; 330; Dynamic Bilateral Monopoly; Markov-Perfect Equilibrium; Depletable Resources; Energy; Alternative Fuels; Oil Dependence